“Zero Dose” Children in the Democratic Republic of the Congo: How Many and Who Are They? - Daniel Katuashi Ishoso; M. Carolina Danovaro-Holliday; Aimé Mwana-Wabene Cikomola; Christophe Luhata Lungayo; Jean-Crispin Mukendi; Dieudonné Mwamba; Christian Ngandu; Eric Mafuta; Paul Samson Lusamba Dikassa; Aimée Lulebo; Deo Manirakiza; Franck-Fortune Mboussou; et al. (Vaccines, 2023)
(1) Background: The Democratic Republic of the Congo (DRC) is one of the countries with the highest number of never vaccinated or “zero-dose” (ZD) children in the world. This study was conducted to examine the proportion of ZD children and associated factors in the DRC. (2) Methods: Child and household data from a provincial-level vaccination coverage survey conducted between November 2021–February 2021 and 2022 were used. ZD was defined as a child aged 12 to 23 months who had not received any dose of pentavalent (diphtheria-tetanus-pertussis-Haemophilus influenzae type b (Hib)-Hepatitis B) vaccine (by card or recall). The proportion of ZD children was calculated and associated factors were explored using logistic regression, taking into account the complex sampling approach. (3) Results: The study included 51,054 children. The proportion of ZD children was 19.1% (95%CI: 19.0–19.2%); ZD ranged from 62.4% in Tshopo to 2.4% in Haut Lomami. After adjustment, being ZD was associated with low level of maternal education and having a young mother/guardian (aged ≤ 19 years); religious affiliation (willful failure to disclose religious affiliation as the highest associated factor compared to being Catholic, followed by Muslims, revival/independent church, Kimbanguist, Protestant); proxies for wealth such as not having a telephone or a radio; having to pay for a vaccination card or for another immunization-related service; not being able to name any vaccine-preventable disease. A child’s lack of civil registration was also associated with being ZD. (4) Conclusions: In 2021, one in five children aged 12–23 months in DRC had never been vaccinated. The factors associated with being a ZD child suggest inequalities in vaccination that must be further explored to better target appropriate interventions.